Los monumentos de la lengua mesápica y los problemas de la edición de inscripciones en lenguas fragmentariamente atestiguadas - Hoz, Javier de (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2005)
1. Presentation of MLM. 2. What we know about Messapian language and epigraphy. 3. Analysis of MLM. 4. On some problems of editing epigraphic corpora.
Keywords: Ancient Italy; Iapyges; Messapic; Messapian inscriptions; Apulia; Ancient Calabria; Ancient Puglia; Indo-European studies; epigraphy; epigraphic corpora